Verbatim Record of the Sixtieth Meeting (Closed) - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary Consideration of the report. Witness VVV was a member of Parliament and member of the Smallholders' Party. In 1948 he was arrested and spent seven years in prison. He spoke about the 1947 election, the outbreak of the revolution and the fourteen points, and the conditions in Hungary after the revolution. Witness WWW, the only member of the Greater Budapest Central Workers' Council who was outside Hungary, spoke about the organization and work of the council and the trade unions. The committee asked him about living standards in Hungary and the export of uranium.